3D Crack Behavior in the Orthopedic Cement Mantle of a Total Hip Replacement. Issue 3 (3rd October 2014) - Sahli, Abderahmen; Benbarek, Smail; Wayne, Steven; Bachir Bouiadjra, Bel-Abbes; Serier, Boualem
Abstract : The total hip replacement is an operation that replaces a diseased hip with a mechanical articulation. Both components of the mechanical articulation (stem and the cup) are bonded to bone using orthopedic cement, whose reliability determines the longevity of the implant. The cement around the metallic stem forms a mantle whose strength and toughness determine its resistance to fatigue and failure by fracture. Typical cements are acrylic polymers that often suffer from internal cracks and other defects created during polymerization. This study is a systematic analysis of preexisting 3D crack behavior in the orthopedic cement mantle when subjected to external body forces. Different crack orientations and angular positions around the mantle are studied to identify which locations will propagate the crack. This is accomplished by a global stress analysis of the mantle followed by a failure analysis. Amongst others, the existence of a crack in the proximal region of the orthopedic cement is identified as a critical area, especially in the lateral sides of the stem in the radial direction.